1978
DOI: 10.1111/j.1365-2222.1978.tb00461.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ageing on IgE‐mediated reactions in allergic patients

Abstract: The influence of age and sex has been evaluated in 326 allergic patients on the following parameters: total serum IgE concentration, serum concentration of specific IgE antibodies against seventeen common allergens, mean number of positive allergens, absolute numbers of circulating eosinophils, corticosteroid dependence and response to sodium cromoglycate (DSCG). The results indicate that age and sex significantly influence the IgE antibody production in these patients. The data strongly suggests the appearanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 7 publications
1
19
0
Order By: Relevance
“…No direct correlation between age and reactivity was observed. Workers like Kuhr et al (1990) and Hanneuse et al (1978) reported similar results. Although some patients with positive family history to allergic complaints reacted more, the difference in reactivity with the other group was not significant.…”
Section: Discussionsupporting
confidence: 88%
“…No direct correlation between age and reactivity was observed. Workers like Kuhr et al (1990) and Hanneuse et al (1978) reported similar results. Although some patients with positive family history to allergic complaints reacted more, the difference in reactivity with the other group was not significant.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, Hanneuse et al reported a declining trend with age in total serum IgE, circulating eosinophils, mean positive number of RAST as well as mean positive value of RAST to individual allergens that is more pronounced in atopic females than males. [47] Clinically, however, they noted a disconnect with a decreased corticosteroid requirement in younger atopic patients than older patients despite an increased prevalence in markers of atopy in the younger cohort. Raherison and colleagues found a strong relationship between percent positive RAST scores (40-42% in Asthma and/or allergic rhinitis versus 7% in healthy) and clinical symptoms of allergic rhinitis and asthma in elderly patients.…”
Section: Clinical Implications Of Atopy On Agingmentioning
confidence: 99%
“…Concerning allergic diseases, the incidence of onset of allergic symptoms, as well as their severity seems to decrease with age [1]. Atopy is a relatively common, adverse humoral immune system response to common environmental agents (allergens) involving the production of allergen-specific IgE.…”
Section: Introductionmentioning
confidence: 99%